2006
DOI: 10.1113/jphysiol.2006.115675
|View full text |Cite
|
Sign up to set email alerts
|

Similar nociceptive afferents mediate psychophysical and electrophysiological responses to heat stimulation of glabrous and hairy skin in humans

Abstract: The ability to perceive and withdraw rapidly from noxious environmental stimuli is crucial for survival. When heat stimuli are applied to primate hairy skin, first pain sensation is mediated by type-II A-fibre nociceptors (II-AMHs). In contrast, the reported absence of first pain and II-AMH microneurographical responses when heat stimuli are applied to the hand palm has led to the notion that II-AMHs are lacking in this primate glabrous skin. The aim of this study was to assess the effect of hairy and glabrous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
137
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 150 publications
(146 citation statements)
references
References 29 publications
7
137
1
1
Order By: Relevance
“…hairy) and palm (i.e. glabrous) of human hand, as delivered via non-contact laser stimulation, induced qualitatively and quantitatively similar heat-pain sensations and brain potentials in healthy humans (161). Contrary to laser stimulation, contact heat stimulation of the palm of the hand (performed with a thermal probe) had to be significantly higher than that of the dorsum in order to obtain comparable heat-pain sensations.…”
Section: Role Of Skin Region Stimulatedmentioning
confidence: 99%
See 2 more Smart Citations
“…hairy) and palm (i.e. glabrous) of human hand, as delivered via non-contact laser stimulation, induced qualitatively and quantitatively similar heat-pain sensations and brain potentials in healthy humans (161). Contrary to laser stimulation, contact heat stimulation of the palm of the hand (performed with a thermal probe) had to be significantly higher than that of the dorsum in order to obtain comparable heat-pain sensations.…”
Section: Role Of Skin Region Stimulatedmentioning
confidence: 99%
“…Such differences in thermal sensitivity have long been suggested to dependent upon potential differences in sensory innervation between hairy and glabrous skin sites. However, recent evidence has indicated that, rather than being determined by physiological differences only (160), previously observed differences in thermal sensitivity between hairy and glabrous skin could have been partly determined by biophysical factors related to the properties of these types of skin (161). As opposed to hairy skin, glabrous skin presents a thicker stratum corneum (i.e.…”
Section: Role Of Skin Region Stimulatedmentioning
confidence: 99%
See 1 more Smart Citation
“…Noxious radiant-heat stimuli were generated by an infrared neodymium yttrium aluminum perovskite laser with a wavelength of 1.34 m (Electronical Engineering). These laser pulses activate directly and selectively nociceptive terminals located in the most superficial skin layers (Baumgärtner et al, 2005;Iannetti et al, 2006). Laser pulses were directed to the dorsum of the right and left hands, in two separate sessions performed on the same day.…”
Section: Participants Experimental Paradigm and Eeg Recordingmentioning
confidence: 99%
“…These laser pulses activate directly and selectively nociceptive terminals located in the most superficial skin layers [21][22]. Laser pulses were directed to the dorsum of the right and left hands, in two separate sessions performed on the same day.…”
Section: Experimental Design and Eeg Recordingmentioning
confidence: 99%